Crowdfunding and the democratization of finance - Davis, Mark 1978-; Davis, Bruce ca. 20./21. Jh (Bristol shorts research, 2022)
A unique collaboration between an academic and a practitioner, this book tells the story of money, from ancient Athens to the Bitcoin revolution, to explain how crowdfunding is the way for people to reclaim the power of their money in pursuit of a fairer and greener society